Mandibular asymmetry: A proposal of radiographic analysis with public domain software - Alexandre Durval Lemos; Cintia Regina Tornisiello Katz; Mônica Vilela Heimer; Aronita Rosenblatt (Dental Press Editora, 2014)
OBJECTIVE: This preliminary study aimed to propose a new analysis of digital panoramic radiographs for a differential diagnosis between functional and morphological mandibular asymmetry in children with and without unilateral posterior crossbite. METHODS: Analysis is based on linear and angular measurements taken from nine anatomic points, demarcated in sequence directly on digital images. A specific plug-in was developed as part of a larger public domain image processing software (ImageJ) to automate and facilitate measurements. Since panoramic radiographs are typically subject to magnification differences between the right and left sides, horizontal linear measurements were adjusted for greater accuracy in both sides by means of a Distortion Factor (DF). In order to provide a preliminary assessment of proposed analysis and the developed plug-in, radiographs of ten patients (5 with unilateral posterior crossbite and 5 with normal occlusion) were analyzed. RESULTS: Considerable divergence was found between the right and left sides in the measurements of mandibular length and position of condyles in patients with unilateral posterior crossbite in comparison to individuals with normal occlusion. CONCLUSION: Although there are more effective and accurate diagnostic methods, panoramic radiography is still widespread, especially in emerging countries. This study presented initial evidence that the proposed analysis can be an important resource for planning early orthodontic intervention and, thus, avoid progression of asymmetries and their consequences.